Advantages and risks of extrajudicial recognition of socio-affective affiliation - Neumann, Rafaela; Karvat, Jaciel Santos (Seven Editora, 2023)
This work aims to research and contrast the advantages and risks of extrajudicial recognition of socio-affective affiliation. With Provision 63 of the CNJ, amended by Provision 83 of 2019, the extrajudicial route, through civil registrars, became able to recognize socio-affective affiliation. Despite the presumed advantages of this extrajudicial procedure, it is possible to identify some weaknesses, especially concerning the analysis of supporting documents, when a burden hitherto exclusive to the magistrates is given to the registrar. Therefore, the guiding question of this work is the verification of the advantages and risks of the extrajudicial recognition of socio-affective affiliation. The approach is qualitative and the main methodological tools are bibliographic and documentary research, in addition to collecting information about the procedure that is carried out at the Civil Registry Office of the Municipality of Rio Negrinho. The results indicate that the recognition of socio-affective affiliation through the extrajudicial route is a procedure that has numerous advantages over the judicial procedure for this purpose. Despite the risks in proving the link, the registrar has at his disposal several possible means of proof, which gives a reasonable degree of reliability to the decision. DOI:https://doi.org/10.56238/alookdevelopv1-092